2009
DOI: 10.1210/jc.2008-2324
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Bone Turnover Despite Persistent Secondary Hyperparathyroidism during Prolonged Treatment with Imatinib

Abstract: Long-term treatment with imatinib leads to persistent mild secondary hyperparathyroidism. Despite this, bone turnover is decreased, and bone density is stable or increased. Evaluation of the skeletal actions and safety of imatinib during longer-term therapy is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
1
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 30 publications
2
55
1
1
Order By: Relevance
“…(17) Additionally, two subsequent studies showed that CML patients undergoing imatinib therapy exhibited small increases in regional BMD. (40,41) In support of these findings, several groups have shown that CML and gastrointestinal stromal tumor (GIST) patients undergoing imatinib treatment display altered serum biochemistry that is suggestive of changes in bone remodeling. In particular, a number of studies show that decreased levels of serum phosphate occur as early as 3 months following initiation of imatinib treatment in CML and GIST patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…(17) Additionally, two subsequent studies showed that CML patients undergoing imatinib therapy exhibited small increases in regional BMD. (40,41) In support of these findings, several groups have shown that CML and gastrointestinal stromal tumor (GIST) patients undergoing imatinib treatment display altered serum biochemistry that is suggestive of changes in bone remodeling. In particular, a number of studies show that decreased levels of serum phosphate occur as early as 3 months following initiation of imatinib treatment in CML and GIST patients.…”
Section: Discussionmentioning
confidence: 91%
“…(42,45,46) Decreased serum phosphate levels in imatinib-treated patients are associated with increased serum parathyroid hormone levels, decreased levels of the bone resorption marker CTX-1, and in at least some cases, a decrease in serum calcium levels. (17,40,41,(43)(44)(45) To our knowledge, there have been no published reports suggesting that changes in bone remodeling occur in patients receiving dasatinib. However, grade 3 or 4 hypophosphatemia has been reported in 11% of dasatinib-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic fusion protein MOZ-TIF2 is one of several fusion products resulting from reciprocal chromosomal rearrangements in the MOZ/MYST3/KAT6A gene in acute myeloid leukemia. 1 Previous studies have shown that MOZ-TIF2 transforms haematopoietic progenitors 2,3 and induces acute myeloid leukemia in a murine bone marrow transplant model. 2,4 MOZ-TIF2 induces widespread changes in histone acetylation, 3,5 subverting the development of haematopoietic progenitors towards leukaemia.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…[1][2][3] Considering that dasatinib and imatinib partly inhibit the same tyrosine kinases, similar effects on bone metabolism might be seen with the second-generation TKI dasatinib.…”
mentioning
confidence: 92%
See 1 more Smart Citation